Aktivitas Antibakteri Ekstrak Etanol Daun Stevia (Stevia Rebaudiana) terhadap Bakteri Uji Penyebab Infeksi Saluran Pencernaan secara Klt-Bioautografi - Hasrawati, Andi; Rusli; Dwi Kurnia Aslam (Jurnal Kesehatan Cendikia Jenius, 2024)
Stevia leaves (Stevia rebaudiana) are one of the sugar substitute plants in Indonesia that contain steviol glycosides. This study aims to determine the antibacterial activity of ethanol extract of stevia leaves (Stevia rebaudiana) against test bacteria that cause digestive tract infections using the TLC-Bioautography method. This research method was carried out experimentally to test the antibacterial activity of stevia leaves using TLC-Bioautography. The results of this study showed that ethanol extract of stevia leaves can inhibit the growth of test bacteria Salmonella typhi, Shigella dysenteriae, Escherichia coli and Vibrio cholerae. The bioautogram profile of antibacterial activity of ethanol extract of stevia leaves (Stevia rebaudiana) using TLC- on the test bacteria Shigella dysenteriae obtained 2 active spots with Rf values ​​of 0.88 and 0.27. In Salmonella typhi bacteria, 3 active spots were obtained with Rf values ​​of 0.88; 0.57 and 0.27. In Escherichia coli bacteria, 3 active spots were obtained with Rf values ​​of 0.88; 0.57 and 0.27. In Vibrio cholerae bacteria, 3 active spots were obtained with Rf values ​​of 0.88; 0.57 and 0.27. It can be concluded that stevia leaves (Stevia rebaudiana) have antibacterial activity. It is recommended to confirm the antibacterial activity of ethanol extract of stevia leaves (Stevia rebaudiana) against bacteria of several different infectious disorders.